2005
DOI: 10.1007/s00330-005-0016-1
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the pelvis at 3 T: very high spatial resolution with sensitivity encoding and flip-angle sweep technique in clinically acceptable scan time

Abstract: High spatial resolution pelvic studies with high image quality can be obtained at 3 T in acceptable scan time. The higher spatial resolution that is feasible at 3 T also provides more clinically relevant information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Their study revealed comparable image contrast for the 1.5-T and 3-T protocols. 1 They concluded that there was no difference between the two systems in tumor diagnosis and staging. However, no case of endometrial cancer was considered in their population.…”
Section: Discussionmentioning
confidence: 99%
“…Their study revealed comparable image contrast for the 1.5-T and 3-T protocols. 1 They concluded that there was no difference between the two systems in tumor diagnosis and staging. However, no case of endometrial cancer was considered in their population.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we reduced the flip angle on all sequences at 3.0T to avoid exceeding the SAR limits, and MRCP at 3.0T was performed safely in all volunteers without any complications. Flip-angle reduction is another promising technique, and its clinical utility was suggested by a recent report (12). Although the reduction of flip angle may induce changes in image contrast between fluid and soft tissue, in our study the bile and pancreatic ducts were clearly visualized by MRCP images on all sequences at 3.0T, and the CNR of heavily T2W images obtained with breath-held multislice HASTE with a reduced flip angle at 3.0T was not inferior to that of heavily T2W images obtained with a higher flip angle at 1.5T.…”
Section: Discussionmentioning
confidence: 99%
“…The higher fi eld strength provides a higher signalto-noise ratio and spatial resolution ( 15 ), and these may help improve diagnostic accuracy for small lesions compared with 1.5 T ( 16 ). However, the higher fi eld strength also comes with greater fi eld inhomogeneity, stronger susceptibility effects, longer T1 relaxation times, larger chemical shift, and higher radiofrequency deposition ( 17,18 ), which may cause lower signal in some parts of the image and show less contrast enhancement, which in turn may lead to false-negative diagnoses (19)(20)(21). With all these concerns, clinical breast MR imaging is N eoadjuvant chemotherapy (NAC) is the standard-of-care treatment for locally advanced inoperable breast cancer, but it is increasingly being used for patients with operable cancer ( 1,2 ).…”
Section: Patientsmentioning
confidence: 99%